EVALUASI PENGELOLAAN KEUANGAN DESA (STUDI KASUS PENGELOLAAN KEUANGAN DESA PADA DESA DI KOTA PARIAMAN) - Chairun Amallia; Masyhuri Hamidi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This study aims to determine the aplication of financial management in several villages in Pariaman City and  compare the three villages from the highest, medium and lowest realization levels. Furthmore, this study aims to examine what factors affect the high and low realization  off village spending. This research is a qualitative research through  data reduction method, data display and drawing conclutions and verification is used as a data analysis technique. The results of this study indicate that 3 people in the village appratus still lack understanding of how to manage village finances, what stage should be done, and lack of understanding and explain what evaluation tools are used at each stage of financial management. Factors that influence the achievement of village expenditure realization are strong collaboration between village officials, discipline of village officials, and village’s human resources. In research conducted in three villages in Pariaman City, it can be judged that with such a large responsibility from the village, but not supported by adequate human resources and high work commitment.